Toksisitas Ekstrak Etanol Mangifera foetida L. sebagai Pengkelat Besi Ditinjau dari LD50 dan Komponen Sel Darah - Wahyuni, Tri; Sari, Santi Purna; Estuningtyas, Ari; Freisleben, HJ (Pharmaceutical Sciences and Research, 2015)
Ethanolic extract of bacang mango leaves (Mangifera foetida L.) decreased iron concentration in blood Sprague dawley rats that had been induced iron overload. The aim of this experiment was to determine acute toxicity (LD50) value of ethanolic extract of M.foetida by weil method and its effect to blood component. This study was conducted by employing a complete random design using 25 male and 25 female mice of DDY strain which devided into 5 groups. The first group until fourth group were administered ethanolic extract of M.foetida with dose variation which suspension in aquadest orally. The fifth group was control that administered aquadest. The LD50 was determined by the total of death on all group. LD50 value of the extract showed no death in the biggest doses (13.013 g/kg). The examination was continued with measured blood count (erythrocites, trombocytes, leukocytes, and haemoglobin concentration). It was shown that the extract at dose 1.626; 3.253; 6.506 and 13.013 g/kg unchanged the blood count measurement.